Identifying the roots of Green Civil War over utility-scale solar energy projects on public lands across the American Southwest. Issue 6 (2nd November 2017) - Mulvaney, Dustin
ABSTRACT: Utility-scale solar energy (USSE) development is an emerging cause of land use change across the American Southwest. Many proposed projects in the region have encountered resistance from environmental groups because of concern about endangered, threatened, and special status species. Projects have also faced resistance from impacted local communities and Native American tribes. This research documents land use conflicts that surfaced during the initial wave of USSE development from 2009 to 2015. The goal is to identify potential roots of land use conflict over renewable energy development, to help explain why there is consistent support for renewables in general, but widespread opposition to projects during the proposal and development stages. The primary data presented include public comments to formal rule-making processes, semi-structured interviews conducted from 2009 to 2013, and various media sources. The paper concludes describing emerging planning frameworks that identify sites for USSE with fewer land use conflicts.